Pengaruh Edukasi Informasi Berbasis Media Sosial Terhadap Pengetahuan Kanker Payudara Pada Wanita Usia Subur - Dian Anggraini; Dewi Marfuah; Gina Nurdina; Dita Zharifah (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2021)
Breast cancer is a type of malignant tumor which is still the number one killer for women. In Indonesia, it is estimated that 51,136 women were diagnosed with breast cancer in 2015. The limited knowledge of women of childbearing age about what breast cancer is and how to detect it is one of the reasons why breast cancer continues to increase. Knowledge is very important in the prevention of breast cancer. With good knowledge, it is expected that women of childbearing age are able to motivate themselves and even those around them to do breast self-examination. One way to increase knowledge is by providing education. Providing education can be done by utilizing social media, namely Instagram. Instagram has a strong appeal to share information resources with all people. Through Instagram, respondents not only hear the material delivered but can also see posts in the form of attractive and effective images and videos. This study aims to determine the effect of social media-based information education on breast cancer knowledge in women of childbearing age. Methods: This research is a quantitative research with Pre-Experimental design with Two Group Pre-Posttest Design, the sampling technique is convenience sampling. conducted in May-July 2021, the research sample was 60 women of childbearing age. Data analysis using Paired Sample T-test and ANCOVA. There is a significant difference between the knowledge scores of breast cancer prevention in women of childbearing age. who received social media-based information education intervention compared to the group that did not get the intervention with p-value = 0.000 (p < ? 0,05). This intervention regarding social media-based information education has an effect on increasing knowledge of breast cancer in women of childbearing age.